Ice jackets are cool - Martina, D. T.; Hahn, A. G.; Ryan-Tanner, R.; Yates, K. (Sportscience, 1998)
Scientists at the Australian Institute of Sport have developed a jacket for pre-cooling athletes before endurance events in the heat. The jackets are made from wet-suit material and are packed with ice. Athletes who wore the jackets at the Atlanta Olympics probably boosted their output power by 1-2%.